2014
DOI: 10.1371/journal.pone.0106398
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Local and Landscape-Level Characteristics on the Abundance of Forest Birds in Early-Successional Habitats during the Post-Fledging Season in Western Massachusetts

Abstract: Many species of mature forest-nesting birds (“forest birds”) undergo a pronounced shift in habitat use during the post-fledging period and move from their forest nesting sites into areas of early-successional vegetation. Mortality is high during this period, thus understanding the resource requirements of post-fledging birds has implications for conservation. Efforts to identify predictors of abundance of forest birds in patches of early-successional habitats have so far been equivocal, yet these previous stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…To determine whether birds selected fruits of either native or invasive species, we conducted foraging observations from July through early September at 10 sites during 2007 and 5 sites during 2008 (4 of which were also surveyed in 2007). This period coincided with the peak diversity and abundance of native and nonnative fruits in the region (Stiles 1980), as well as the peak in the abundance and diversity of birds in shrubland habitats, which are utilized by both shrubland and forest bird species (Labbe and King 2014). The study period also coincided with the postfledging or postbreeding seasonal lifecycle phase that occurs after nesting and before the onset of migration (Faaborg et al 1996; Vega Rivera et al 1998, 1999) and associated deposition of subcutaneous fat (Rappole and Ballard 1987).…”
Section: Methodsmentioning
confidence: 87%
“…To determine whether birds selected fruits of either native or invasive species, we conducted foraging observations from July through early September at 10 sites during 2007 and 5 sites during 2008 (4 of which were also surveyed in 2007). This period coincided with the peak diversity and abundance of native and nonnative fruits in the region (Stiles 1980), as well as the peak in the abundance and diversity of birds in shrubland habitats, which are utilized by both shrubland and forest bird species (Labbe and King 2014). The study period also coincided with the postfledging or postbreeding seasonal lifecycle phase that occurs after nesting and before the onset of migration (Faaborg et al 1996; Vega Rivera et al 1998, 1999) and associated deposition of subcutaneous fat (Rappole and Ballard 1987).…”
Section: Methodsmentioning
confidence: 87%
“…However, the abundance of Red-winged Blackbird (a facultative wetland species that also nests in uplands) declined with the amount of wetlands in the landscape, whereas the abundance of the Yellow-headed Blackbird (an obligate wetland species that only nests in wetlands) declined in wetlands as the amount of grassland in the landscape increased. Many other studies have demonstrated the importance of both local-and landscapelevel factors on bird communities (for example, Naugle and others, 2000a; Cunningham and Johnson, 2006;Tsai, 2007;Niemuth and others, 2008;Clough and others, 2009;Roselli and Stiles, 2012;Labbe and King, 2014;Galitsky and Lawler, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Our study focused only on avian abundance during the nesting period, and both mature‐forest and shrubland birds use early‐successional, harvested stands extensively during the post‐fledging period (Akresh et al, 2009; Chandler et al, 2012; Labbe & King, 2014). More species‐specific studies are needed in order to incorporate the post‐fledging period into meta‐analyses of bird relationships with tree retention (Cox et al, 2014).…”
Section: Discussionmentioning
confidence: 99%